2015
DOI: 10.1155/2015/751013
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Primes Human Bone Marrow CD34+ Cells for Erythroid Differentiation

Abstract: Arsenic trioxide exhibits therapeutic effects on certain blood malignancies, at least partly by modulating cell differentiation. Previous in vitro studies in human hematopoietic progenitor cells have suggested that arsenic may inhibit erythroid differentiation. However, these effects were all observed in the presence of arsenic compounds, while the concomitant cytostatic and cytotoxic actions of arsenic might mask a prodifferentiating activity. To eliminate the potential impacts of the cytostatic and cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The RDW showed little change among the different groups. The first among the possible reasons for these findings is that the total amount of arsenic entering the body by respiration was limited [15]; second, the differentiation of RBCs in the bone marrow hematopoietic system fully compensated for the effects of the arsenic; third, arsenic induced eryptosis was characterized by cell shrinkage [16]; and lastly, the effects on differentiation of bone marrow erythrocytes had not yet appeared [17]. In contrast to the results reported by Luo et al [18], RDW was significantly decreased in the HD group at 12 h. It is likely that because arsenic and phosphorus are of the same group and have the same valence state, they have a competitive relationship in metabolism and that arsenic thus directly inhibits ATPase activity on the erythrocyte membrane, affecting glucose metabolism, and then affecting the morphology of RBCs [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The RDW showed little change among the different groups. The first among the possible reasons for these findings is that the total amount of arsenic entering the body by respiration was limited [15]; second, the differentiation of RBCs in the bone marrow hematopoietic system fully compensated for the effects of the arsenic; third, arsenic induced eryptosis was characterized by cell shrinkage [16]; and lastly, the effects on differentiation of bone marrow erythrocytes had not yet appeared [17]. In contrast to the results reported by Luo et al [18], RDW was significantly decreased in the HD group at 12 h. It is likely that because arsenic and phosphorus are of the same group and have the same valence state, they have a competitive relationship in metabolism and that arsenic thus directly inhibits ATPase activity on the erythrocyte membrane, affecting glucose metabolism, and then affecting the morphology of RBCs [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In studies using CD34 + cells isolated from chronic myeloid leukemia patient bone marrow, sub-toxic levels of arsenic trioxide enhanced or primed erythroid colony forming activity. Additionally the same study demonstrated sub-toxic levels of arsenic trioxide inhibited globin gene expression in K562 cells, a chronic myelogenous leukemia patient derived erythroid-myeloid precursor cell line 53 . While the effect of arsenic appears biphasic in cell culture this cannot be assumed to be the case in the setting of chronic hemodialysis.…”
Section: Discussionmentioning
confidence: 79%
“…Изменения в крови появляются уже при действии сравнительно малых доз токсических веществ [1] и зачастую являются единственным показателем возникающего заболевания или начала развития осложнений [2]. Сам факт влияния отдельных тяжелых металлов на систему крови описан в литературе [3,4], однако сведения об ответных реакциях гемопоэтической ткани при сочетанной интоксикации противоречивы и недостаточны для четкого определения общих медико-экологических закономерностей токсического влияния природных соединений на организм. Изучение патогенеза металлиндуцированных анемий и поиск возможных путей их коррекции -актуальные задачи для медицинской науки Башкортостана, который занимает второе место в Уральском регионе по промышленному потенциалу и является крупнейшим индустриальным центром России.…”
Section: Introductionunclassified